Aeromonas hydrophila in surface water and their removal using a POU technology for drinking in rural communities - Liliana Botero; Laila Galeano; Luis Javier Montoya; Alexander Machado; John Anthony Byrne; Pilar Fernandez-Ibañez; Margarita Hincapié (Environmental Advances, 2023)
Aeromonas hydrophila is a common emerging pathogenic bacterium in natural waters that affects the quality of drinking water. This becomes a challenge for the development and innovation of alternative technologies that provide safe water to families in rural communities. The present study evaluated the ability to inactivate natural A. hydrophila from surface waters using a drinking water treatment system at the point of use (POU). It is based on 2 thermofused polypropylene filters followed by a UV disinfection lamp, and it was installed in houses in two rural communities in Colombia. Experimental results showed that the POU systems removed A. hydrophila with a log reduction value (LRV) of 3.60 ± 0.02 in the synthetic waters, and removal values greater than 2 LRV in tests performed with natural surface waters with detected naturally occurring Aeromonas and quantified in these communities with LRV of 3.1 ± 0.6 and 2.2 ± 0.6, respectively, with a detection limit of 1 CFU/100mL. The concentrations of E. coli and total coliforms (TC) were also monitored in 54 homes all equipped with the above-described POU systems for 12 months. Given the efficacy found in this study and the availability, accessibility, and affordability of the elements used to design and manufacture the POU systems, it is feasible to propose their use to provide safe water to vulnerable families living in rural communities that lack water treatment systems.